Design and Build an IoT Based Reading Room Visitor Monitoring System for the Department of Electrical Engineering - Napitu, Gita Masito (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2024)
The reading room is one of the places frequented by students. Students can use this room for various activities such as reading books, looking for materials, independent study, and other activities. The increasing number of visitors in the room can affect the availability of space which can cause inconvenience between visitors and limited facilities that can hamper the activities to be carried out. Therefore, regular monitoring of the room is needed so that the room can be used optimally. In this study, researchers proposed a reading room visitor monitoring system tool majoring in IoT-based electrical engineering. This tool utilizes a single microcontroller, namely NodeMCU Esp8266 with the features offered, namely monitoring the number of visitors entering and leaving the room, the total number of visitors who are in the room, and the status of room availability. This tool is also equipped with red and green indicator lights as an indicator of room availability and a buzzer as an alarm if the room condition is full. The monitoring results are displayed on the LCD and utilize the IoT platform, namely in the application that displays monitoring results via a smartphone that can be accessed regularly. The sensors used in this study include Ultrasonic sensors and PIR sensors. The purpose of this research is to produce IoT-based reading room visitor monitoring tools and test the performance of the tools. In this study, the visitor monitoring tool that was made worked well with an average error of 0.031. Keywords: IoT, Monitoring Visitors, Applications